Ma’had Aly Lecturers’ Research and Publication Activities: Challenges and Prospects - Purnomo, Pungki; Wenny, Lili Sudria; Farida, Ida; Hamdani, Fadhilatul (Buletin Al-Turas, 2024)
PurposeIn Islamic higher education, Ma'had Aly lecturers rarely performed research and publication activities. The study aimed to explore Ma’had Aly lecturers’ in conducting research and publishing scholarly works activities.MethodThis qualitative study used a case study design whose data collection techniques utilized in-depth interviews and a review of relevant articles. The informants comprised four Ma'had Aly lecturers taken purposively.Results/findingsThe findings revealed problems that caused lecturer Ma'had Aly to rarely carry out research and publication activities. In terms of personnel problems, apart from the fact that Ma'had Aly lecturers had not only adequate knowledge regarding research and publications, but they were also burdened with a heavy teaching load and other non-academic activities. Meanwhile, in terms of institutional problems, Ma'had Aly could not create a conducive atmosphere for lecturers to perform research and publication activities.Conclusion Research and publication are important for Ma'had Aly lecturers for their professional development. Therefore, both Ma'had Aly management and the Ministry of Religion should make various efforts to accelerate the research and publication competency improvement of Ma'had Aly lecturers.